Particle Size of Dry-rolled Corn Affects Starch Digestibility but Not Feedlot Performance - E. F. Schwandt; J. Wagner; T. Engle; S. J. Bartle; D. U. Thomson; C. D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2017)
Dry-rolling corn is a common practice in feedlots located in the Midwestern and Northern Plains regions of the United States. Optimizing total digestive tract starch utilization in diets containing dry-rolled corn is essential for maximizing efficiency. However, recommendations often suggest that grain be coarsely cracked to avoid producing an excessive amount of fine material that could potentially increase the rate of fermentation, reduce rumen pH, and cause digestive disturbances. Wet distillers byproducts may be effectively used as a protein and energy source for feedlot finishing cattle and can replace a portion of the dry-rolled corn in the diet. The average geometric mean particle size of dry-rolled corn across all feedyards (n = 31) was 0.179 ± 0.035 in. with a range of 0.085 to 0.269 in. The objective of this study was to evaluate the effects of dry-rolled corn particle size on animal performance, carcass traits, and starch digestibility in feedlot finishing diets containing 20% wet distillers grains on a dry matter basis.
Keywords: dry rolled corn; feedlot; particle size